Phenylalanine isotope pulse method to measure effect of sepsis on protein breakdown and membrane transport in the pig - Ten Have, Gabriella A. M. (Am J Physiol Endocrinol Metab, 2017)
The primed-continuous (PC) phenylalanine (Phe) stable isotope infusion methodology is often used as a proxy for measuring whole body protein breakdown (WbPB) in sepsis. It is unclear if WbPB data obtained by an easy-to-use single IV Phe isotope pulse administration (PULSE) are comparable to those by PC. Compartmental modeling with PULSE could provide us more insight in WbPB in sepsis. Therefore, in the present study, we compared PULSE with PC as proxy for WbPB in an instrumented pig model with Pseudomonas aeruginosa-induced severe sepsis (Healthy: n = 9; Sepsis: n = 13). Seventeen hours after sepsis induction, we compared the Wb rate of appearance (WbR(a)) of Phe obtained by PC (L-[ring-(13)C(6)]Phe) and PULSE (L-[(15)N]Phe) in arterial plasma using LC-MS/MS and (non)compartmental modeling. PULSE-WbR(a) was highly correlated with PC-WbR(a) (r = 0.732, P < 0.0001) and WbPB (r = 0.897, P < 0.0001) independent of the septic state. PULSE-WbR(a) was 1.6 times higher than PC-WbR(a) (P < 0.001). Compartmental and noncompartmental PULSE modeling provide comparable WbR(a) values, although compartmental modeling was more sensitive. WbPB was elevated in sepsis (Healthy: 3,378 ± 103; Sepsis: 4,333 ± 160 nmol·kg BW(−1)·min(−1), P = 0.0002). With PULSE, sepsis was characterized by an increase of the metabolic shunting (Healthy: 3,021 ± 347; Sepsis: 4,233 ± 344 nmol·kg BW(−1)·min(−1), P = 0.026). Membrane transport capacity was the same. Both PC and PULSE methods are able to assess changes in WbR(a) of plasma Phe reflecting WbPB changes with high sensitivity, independent of the (patho)physiological state. The easy-to-use (non)compartmental PULSE reflects better the real WbPB than PC. With PULSE compartmental analysis, we conclude that the membrane transport capacity for amino acids is not compromised in severe sepsis.